IN - PROSESMETING 'n Nuwe Konsep In Vervaardigingstegnologie - Lane, I.E. (The South African Journal of Industrial Engineering, 2013)
ENGLISH ABSTRACT: Modern electronic and computer systems are impacting the availability performance of production systems. Automated-fault indication equipment has not always given the expected availability benefits, and there is strong evidence in some cases that productivity might have improved if less complex diagnostic support systems were employed. Clearly diagnostic support is both a management and technical problem. Some availability modelling structurers which account for diagnostic support system performance are reviewed. An availability model which conforms to a consistent outage data classification policy is proposed. An example is-given to show how availability returns can be calculated to compare the relative berrefitsof managerial and technical diagnostic support ac~ions. The o~imal deployment of diagnostic support throughout the life cycle of large scale or complex production systems ean be achieved with the help of the proposed decision support model. AFRIKAANSE OPSOMMING: Moderne elektroniese en rekenaarstelsels beinvloed dia beskikbaarheidsprestasie van produksiesisteme. Outomatiese foutdiagnosetoerusting lewer nie altyd die verwagte beskikbaarheidsvQordele nie en daar is in sekere gevalle sterk aanduidings. dat produktiwiteit benadeel word deur die kompleksiteit van diagnostiese steunstelsels. Dit is duidelik dat diagnostiese steun beide n bestuursprobleem enn tegniese probleem is. -Sekere beskikbaarheidsmodelleringstrukture wat vir die prestasievan diagnostiese steunstelsels yoorsiening maak, word bespreek. n Beskikbaarheidsmodel wat verenigbaar is met n spesifieke stilstand-dataklassifi- ';. kasiebeleid word voorgestel. n Voorbeeldberekening word gegee om aan te toon hoe die relatiewe voordele van bestuursaksies en tegniese aksies ten opsigte van diagnostiese steun vergelyk kan word. Die optimale diagnostjese steunstelselontplooi- ;'.\", ing gedurendedie lewenssiklus van grootskaalse of komplekse produksiesisteme kan behaal word met die hulp van die voorgestelde besluitsteurrmodel.